Catalogue of the Mingana Collection of Manuscripts - Mingana, Alphonse (Kiraz Historical Catalogues Archive, 2006)
This multi-volume set is the catalogue for the famed Mingana Collection of Syriac and Arabic manuscripts. A principal resource for scholars of early Middle Eastern documents, this set describes and summarizes the documents that make up this collection